The measured CSF/plasma donepezil concentration ratio but not individually measured CSF and plasma concentrations significantly increase over 24 h after donepezil treatment in patients with Alzheimer's disease - Valis, Martin; Dlabkova, Alzbeta; Hort, Jakub; Angelucci, Francesco; Pejchal, Jaroslav; Kuca, Kamil; Pavelek, Zbysek; Karasova, Jana Zdarova; Novotny, Michal (Biomedicine & pharmacotherapy, 2023)
BACKGROUND: The acetylcholinesterase inhibitor donepezil is administered as a treatment for Alzheimer's disease (AD). However, the appropriate donepezil dosage is still a matter of debate. METHODS: Forty AD patients receiving 10 mg/day of donepezil were randomly divided into four groups based on the time of plasma and cerebrospinal fluid (CSF) sampling: 6 h (n = 5), 12 h (n = 12), 18 h (n = 6) and 24 h (n = 17) after donepezil administration. High-performance liquid chromatography measured the donepezil concentration in plasma samples and CSF samples collected at 4-time points. RESULTS: Plasma and CSF levels among the groups were not significantly different. Conversely, the CSF/plasma donepezil concentration ratio considerably increased in the 24 h group compared to the 6 h (p < 0.005) and 12 h (p < 0.05) groups. CONCLUSION: The measurement of the CSF/plasma donepezil concentration ratio could be used to better evaluate the optimal dose of donepezil.
Keywords: Donepezil; Piperidines; cholinesterasové inhibitory; Acetylcholinesterase; donepezil; piperidiny; Humans; Indans; lidé; Alzheimer Disease; Alzheimerova nemoc; acetylcholinesterasa; Cholinesterase Inhibitors; indany